DOES NICHE DIVERGENCE ACCOMPANY ALLOPATRIC DIVERGENCE IN APHELOCOMA JAYS AS PREDICTED UNDER ECOLOGICAL SPECIATION?: INSIGHTS FROM TESTS WITH NICHE MODELS - McCormack, John E.; Zellmer, Amanda J.; Knowles, L. Lacey (Evolution, 2010)
The role of ecology in the origin of species has been the subject of long-standing interest to evolutionary biologists. New sources of spatially explicit ecological data allow for large-scale tests of whether speciation is associated with niche divergence or whether closely related species tend to be similar ecologically (niche conservatism). Because of the confounding effects of spatial autocorrelation of environmental variables, we generate null expectations for niche divergence for both an ecologicalniche modeling and a multivariate approach to address the question: do allopatrically distributed taxa occupy similar niches? In a classic system for the study of niche evolution—the Aphelocoma jays—we show that there is little evidence for niche divergence among Mexican Jay (A. ultramarina) lineages in the process of speciation, contrary to previous results. In contrast, Aphelocoma species that exist in partial sympatry in some regions show evidence for niche divergence. Our approach is widely applicable to the many cases of allopatric lineages in the beginning stages of speciation. These results do not support an ecological speciation model for Mexican Jay lineages because, in most cases, the allopatric environments they occupy are not significantly more divergent than expected under a null model.